2021
DOI: 10.21511/ppm.19(4).2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Do sustainability reporting conduct and corporate governance attributes relate? Empirical evidence from China

Abstract: Adopting agency and stakeholders theories, this study aims to investigate the relationship between corporate governance attributes (board size, board independence, female directors, and CEO duality) and sustainability reporting conduct in China. The empirical analysis is based on a sample of 10,330 firm-year observations of Chinese listed companies over the period from 2015 to 2018. Data are supplied by WIND and CSMAR databases, whilst regression analysis is applied to test the hypotheses. Results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Consistent with existing literature (Bian et al, 2023;Chen et al, 2001;Cullinan et al, 2012;Lin & Liu, 2009;Nguyen et al, 2022;Pasko, Zhang, et al, 2021), the study affirms the significance of ownership concentration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with existing literature (Bian et al, 2023;Chen et al, 2001;Cullinan et al, 2012;Lin & Liu, 2009;Nguyen et al, 2022;Pasko, Zhang, et al, 2021), the study affirms the significance of ownership concentration.…”
Section: Discussionsupporting
confidence: 89%
“…This self-interested disclosure of social information is posited to enhance management welfare (Ness & Mirza, 1991). Additionally, agency theory explains voluntary CSR disclosure as a means to alleviate information asymmetry, reduce opportunistic behavior, and lower capital costs (Mio et al, 2020;Pasko, Zhang, et al, 2021;Tyson & Adams, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of studies on the relationship between CEO duality and environmental disclosure have been inconsistent. While some studies support the conclusion that CEO duality has no significant impact on environmental disclosure (Kumari et al, 2022; Lagasio & Cucari, 2019; Pasko et al, 2021), others have found a positive relationship between duality and environmental disclosure in Indian family‐controlled firms (Oware & Awunyo‐Vitor, 2021). On the other hand, a number of studies have reported a negative relationship between CEO duality and environmental reporting (Hamidah & Arisukma, 2020; Husted & de Sousa‐Filho, 2019; Lagasio & Cucari, 2019; Nuskiya et al, 2021).…”
Section: Slr Resultsmentioning
confidence: 99%
“…Sustainability reporting as a vehicle for environmental and social disclosures is a key tool for strengthening transparency and informing wider stakeholders about companies' short-and long-term strategies, actions and policies regarding the environment firms operate (Adams, Managerial entrenchment as a phenomenon closely related to SR is also considered widely (Garcia-Sanchez et al, 2020; Surroca et al, 2020). In fact, the very relationship SR-CG this study is studying is being extensively researched as well (Jain & Jamali, 2016;Jizi, 2017;Pasko et al, 2021e). Zaman et al (2022) indicates that researchers approach this issue from different points of view, although, in general, two broad approaches can be distinguished: 1) SR as a function of CG; and 2) CG as a function of SR (Zaman et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In turn, the issue of corporate governance (CG) has for a long time attracted the interests of researchers as in essence good management is at the core of companies' success (Makarenko et al, 2020;Masud et al, 2018;Pasko et al, 2021e;Tibiletti et al, 2020). Governance permeates all corners of firms, therefore sustainability reporting practices as well is an issue that is decided by boards of directors as the supreme governing body in the decision-making process of companies (Pasko et al, 2021e;Tibiletti et al, 2020). Undoubtedly, the connection between the governance structure and sustainability reporting policies is fundamental to shaping the companies' strategic vision (Sokil et al, 2020;Tibiletti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%